Konseptualisasi Peningkatan Mutu Pendidikan Tinggi melalui Total Quality Management (TQM) - Imam Azhar (Education for Islamic Studies Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2019)
Total Quality Management is a philosophy of continous improvement, which can provide any educational institution with 3 set of practical tools for meeting and exceeding present and future customers needs, wants and expectation. In modern concept, the higher education is service industrial that should pay any attention and focus on customers needs, wants and expectations that is students themselves and their prospective jobs. The implementation concept of TQM in higher education will be successful if it is supported by involving and empowering the employees at all levels of institution, such as; decision making and problem solving, There must be a strategic planning, as the engine of quality improvement to guide the running of institution in realizing the customers satisfaction, good and visoned management as the main factor of quality improvement process, and forming an effective team work for quality.